Punctulini (Hemiptera: Cicadellidae: Deltocephalinae), a new leafhopper tribe from the Oriental region and Pacific Islands - Dai, W.; Zahniser, J.n.; Viraktamath, C.a.; Webb, M.d. (Zootaxa, 2017)
A new tribe of the leafhopper subfamily Deltocephalinae, Punctulini tribe nov., from China, India, Thailand, and Fiji is described and includes three new genera and five new species: Punctulus gen. nov. includes P. tumidifrons sp. nov. from China, P. manipurensis from India, and P. lobatus sp. nov. from Thailand; Hirsutula gen. nov. includes H. rubrifrons sp. nov. from Thailand; and Taveunius gen. nov. includes T. megapunctatus sp. nov., from Fiji. A key to the genera of Punctulini is provided. Observations on the shared morphological characters of Punctulini with the superficially similar tribe Magnentiini, and with Vartini to which it is found to be related based on phylogenetic analyses of morphological and molecular data including newly available sequences and analyses, are made and discussed. Afrovarta Zahniser 2013 is removed from Vartini and placed in Athysanini, placement nov.